Cap-Assisted Endoscopic Sclerotherapy vs Ligation in the Long-Term Management of Medium Esophageal Varices: A Randomized Trial. Issue 12 (15th December 2020) - Wang, An-Jiang; Zheng, Xue-Lian; Hong, Jun-Bo; Zhong, Jia-Wei; Yu, Hui-Qiang; Zeng, Hai-Ying; Gong, Yue; Gan, Na; Wang, Jian; You, Yu; Guo, Gui-Hai; Xie, Bu-Shan; et al.
Abstract : INTRODUCTION: Compared with endoscopic variceal ligation (EVL), cap-assisted endoscopic sclerotherapy (CAES) improves efficacy in the treatment of small esophageal varices (EVs) but has not been evaluated in the management of medium EVs. The aim of this study was to compare CAES with EVL in the long-term management of patients exhibiting cirrhosis with medium EVs and a history of esophageal variceal bleeding (EVB), with respect to variceal eradication and recurrence, adverse events, rebleeding, and survival. METHODS: Cirrhotic patients with medium EVs and a history of EVB were divided randomly into EVL and CAES groups. EVL or CAES was repeated each month until variceal eradication. Lauromacrogol was used as a sclerosant. Patients were followed up until 1 year after eradication. RESULTS: In total, 240 patients (age: 51.1 ± 10.0 years; men: 70.8%) were included and randomized to the EVL and CAES groups. The recurrence rate of EVs was much lower in the CAES group than in the EVL group (13.0% vs 30.7%, P = 0.001). The predictors for variceal recurrence were eradication by EVL (hazard ratio [HR]: 2.37, P = 0.04), achievement of complete eradication (HR: 0.27, P < 0.001), and nonselective β-blocker response (HR: 0.32, P = 0.003). There was no significant difference in the rates of eradication, rebleeding, requirement for alternative therapy, and mortality or the incidence of complications between groups. DISCUSSION: CAES reduces the recurrence rate of EVs with comparable safety to that of EVL in the long-term management of patients presenting cirrhosis with medium EVs and a history of EVB.